2020
DOI: 10.25259/ijms_44_2020
|View full text |Cite
|
Sign up to set email alerts
|

Demographic profile and spectrum of ultrasonographic findings in medial knee pain: An observational study

Abstract: Objectives: Medial knee pain is a common occurrence in people of various age groups with different conditions involving underlying structures. Ultrasound is used in assessing various complex knee pathologies as relying solely on clinical evaluation can be difficult. There are hardly any studies showing the compartmental analysis of knee pain using ultrasound. This study analyses the demographic profile and associated various ultrasonographic findings in patients with medial knee pain. Material and Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…19 Joshi et al, found baker cyst in 40.63% of the patients. 20 Where as Tarhan and Unlu found baker cyst in 40% and 35% of cases on USG and MRI respectively. 17…”
Section: Discussionmentioning
confidence: 96%
“…19 Joshi et al, found baker cyst in 40.63% of the patients. 20 Where as Tarhan and Unlu found baker cyst in 40% and 35% of cases on USG and MRI respectively. 17…”
Section: Discussionmentioning
confidence: 96%
“…Medial knee pain can be caused by a number of different things, including damage to the medial collateral ligament, degenerative joint disease of the medial compartment, a rupture in the medial meniscus, inflammation of the pes anserine bursa, or medial plica syndrome. Because of the knee's complexity and the difficulty in clinically evaluating it, even the most experienced clinicians utilizing the most stringent clinical procedures do not always arrive at the correct diagnosis (3).…”
Section: Case Presentationmentioning
confidence: 99%